Counseling On Business Opportunities For Farmers And Entrepreneurs In Horticultural Seedling Using Cutting And Grafting Techniques In The Local Market - Juliana Simbolon; Bahagia Sibotolungun Sipahutar; Enda Warista Putra Jaya Sitepu; Muhammad Fauzan Zulazm; Rico Taruna Siregar (Outline Journal of Community Development, 2025)
This extension program focuses on exploring business opportunities for farmer-entrepreneurs in horticultural plant nurseries, utilizing cutting and grafting techniques to serve local markets. The initiative aims to enhance farmers' technical skills, market understanding, and business management capabilities in plant propagation. Through participatory training methods, including hands-on demonstrations and mentoring sessions, participants acquired practical knowledge of vegetative propagation techniques with demonstrated success rates of 80-90%. Market analysis revealed strong local demand for fruit seedlings (particularly citrus, mango, and guava) and ornamental plants, offering profit margins of 40-60%. Key challenges identified include limited access to capital, price fluctuations, and competition from imported seedlings. The program proposed solutions such as improved financing access, strengthened marketing networks, and quality certification systems. Post-intervention results showed significant improvements: 30-50% increase in production capacity, expanded market connections, and 20-40% income growth among participants. The program effectively enhanced both technical competencies and business acumen, creating sustainable livelihood opportunities in the horticultural nursery sector. Recommendations include establishing government-agriculture department partnerships, developing digital marketing platforms, and implementing continuous mentoring programs to ensure long-term business sustainability. These findings highlight the potential of vegetative propagation techniques in empowering small-scale nursery entrepreneurs while contributing to local agricultural development.